Bioreactor cultivation condition for engineered bone tissue: Effect of various bioreactor designs on extra cellular matrix synthesis. Issue 8 (3rd April 2020) - Nokhbatolfoghahaei, Hanieh; Bohlouli, Mahboubeh; Paknejad, Zahrasadat; R. Rad, Maryam; M. Amirabad, Leila; Salehi‐Nik, Nasim; Khani, Mohammad M.; Shahriari, Shayan; Nadjmi, Nasser; Ebrahimpour, Adel; Khojasteh, Arash
Abstract: Dynamic‐based systems are bio‐designed in order to mimic the micro‐environments of the bone tissue. There is limited direct comparison between perfusion and perfusion‐rotation forces in designing a bioreactor. Hence, in current study, we aimed to compare given bioreactors for bone regeneration. Two types of bioreactors including rotating & perfusion and perfusion bioreactors were designed. Mesenchymal stem cells derived from buccal fat pad were loaded on a gelatin/β‐Tricalcium phosphate scaffold. Cell‐scaffold constructs were subjected to different treatment condition and place in either of the bioreactors. Effect of different dynamic conditions on cellular behavior including cell proliferation, cell adhesion, and osteogenic differentiation were assessed. Osteogenic assessment of scaffolds after 24 days revealed that rotating & perfusion bioreactor led to significantly higher expression of OCN and RUNX2 genes and also greater amount of ALP and collagen I protein production compared to static groups and perfusion bioreactor. Observation of cellular sheets which filled the scaffold porosities in SEM images, approved the better cell responses to rotating & perfusion forces of the bioreactor. The outcomes demonstrated that rotating & perfusion bioreactor action on bone regeneration is much preferable than perfusion bioreactor. Therefore, it seems that exertion of multi‐stimuli is more effective for bone engineering.